Modulation of Spatial Attentional Allocation by Computer-Based Cognitive Training during Lacrosse Shooting Performance - Hirao, Takahiro; Masaki, Hiroaki (Frontiers in Psychology, 2018)
It has been reported that repetitive execution of a stimulus-response compatibility (SRC) task attenuates the interference effect of a choice reaction time task, known as a Simon task. We investigated whether attentional control, enhanced by repetitive execution of an SRC task, would reduce the interference effect of a Simon task and could be transferred to lacrosse shooting skills, increasing the likelihood that players would shoot in the direction opposite to the goalie’s initial movement. Female lacrosse players who were matched in terms of age, handedness score, competitive lacrosse playing experience, and playing position, were allocated to the SRC task group (n = 15) or the 2-back training group (n = 14). Participants underwent 10 sessions of 180 trials of a computer-based version of either a Type 2 SRC task or the 2-back task, within four consecutive weeks. Eight practice trials were completed prior to the execution of each task in every training session, during which feedback was provided to confirm accurate mapping between the stimulus and response. Before and after the training phase, both the magnitude of the Simon effect and the lacrosse shooting performance were assessed. After participating in computer-based cognitive training, players did indeed increase the number of shots toward the direction opposite to that of the movement of the goalie. In conclusion, these findings indicate that computer-based cognitive training is beneficial for improving the shooting ability of lacrosse players.